Island queen : a novel - Riley, Vanessa (William Morrow, an imprint of HarperCollinsPublishers, 2021)
"A former slave rises above the harsh realities of being owned and colonialism on Montserrat working hard to buy freedom for herself, her mother, and her sister and becoming an entrepreneur, merchant, hotelier, and planter"--